A diversity and ecology of araceae of Gua lkan, Dabong, Kuala Krai, Kelantan - Abdul Hafidz, Amran (2015)
The study was conducted in Gua Ikan, Kuala Krai, Kelantan. A square plot of (1m x 1m) was set up with the distance for each plot is 2m.The type of plot used in this study is systematic sampling. The result shows twelve species of Araceae has been identified with the most abundant species was Amorphophallus prainii Hook.f. Meanwhile Amydrium medium (Zoll. & Moritzi) Nicolson, Epipremnum giganteum (Roxb.) Schott and Arisaema roxburghii kunth were counted as least abundant species in limestone area. All of species was then were brought back for herbarium collection. The distribution of Araceae was draw by using Geographical Information System (GIS) to show the location of each species.